Meningkatkan Kinerja Karyawan Melalui Iklim Dan Budaya Organisasi - Pulung Puryana; Agung M. Taufik (Jurnal Study and Management Research, 2013)
Organizational business is an organization oriented on achievement of satisfactory profits for all stakeholders, it is reflected in every activity of the organization that is always demanding the effectiveness and efficiency, because one of satisfactory profit indicators is achieving efficiency and effectiveness of organization. Efficiency and effectiveness of the organization is a reflection of an organizational performance. An effective and efficient organizational performance is an entire organization’s hope either business or non-business represented by improvement of employee performance within related organization. The purpose of this study is to determine the performance improvement by creating organizational climate and organizational culture of Cooperatives in Bandung City.The results show that the condition of organizational climate, organizational culture and employee performance are in good condition. Empirically, organizational climate and organizational culture have positive significant influence on employee performance at 28.3%, whereas error variables or beyond the examined variables is 71.7%.Kata Kunci : Employee Performance, Organizational Climate, Organizational Culture.